A comparative study on the response to Epley’s maneuver and betahistine dihydrochloride management among patients with benign paroxysmal positional vertigo - Zaid I. Alsareeh (Al Muthanna University, 2021)
The objective of this study is to evaluate the effectiveness of Epley’s maneuver and Betahistine dihydrochloride on the improvement of patients from BPPV and to comparing the outcome of the use of Betahistine dihydrochloride with the outcome of the use of Epley’s maneuver. This is a prospective and comparative randomized study in Basra Teaching Center of Otolaryngology in which fifty patients were included in this study their age range between (42-65) years, all of them complaining from BPPV. These patients divided into two groups. The first group was treated by Epley’s maneuver and the second group was treated by oral intake of Betahistine dihydrochloride tablet. All patients evaluated at the end of this period by presence or relieving from symptoms and by positive or negative Dix-Hallpike test. A 50 patients were 33 males (66%) and 17 females (34%) and the mean age value for all the patients were in the sixth decade (56.5) years. The improvement from vertigo symptom was statistically significant for the two groups and it was also significant when comparing the two groups which was better in first group and the improvement from associated symptoms like nausea and vomiting and headache was significantly different between the two groups and it was better in the second group. Epley’s maneuver gave a good result in relieving patients of vertigo in patients had BPPV while Betahistine dihydrochloride gave a good result in relieving patients from associated symptoms of BPPV.